Protective role of vitamin E in preventing the adverse effects of bisphenol A on rat testis tissue: A stereological evaluation - Malek Soleimani Mehranjani; Monireh Mahmoodi; Marziye Amjadi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2018)
Introdution: Bisphenol A (BPA) as an environmental pollutant has estrogenic effects and can induce oxidative stress in the testis tissue. The aim of the present study was to investigate the role of vitamin E (Vit E), as a strong antioxidant, on the adverse effect of BPA on adult rat testis tissue. Methods: Male rats (220±15g) were divided into 4 groups (n=6/each): control, Bisphenol A (250 mg/kg/day), Bisphenol A+ Vit E (150 mg/kg/day) and Vit E and orally treated for 56 days. At the end of the treatment, the right testis was removed and after fixation, sectioning, tissue processing and staining with Heidenhain's Azan method was evaluated stereologically. The serum testosterone and malondialdehyde (MDA) levels were also measured. Data were analyzed using one way ANOVA and Tukey's test and the means were considered significantly different (P<0.05). Results: A significant decrease in the total volume of testis, volume and diameter of seminiferous tubule and its height of the germinal epithelium and thickness of the basement membrane, number of spermatids, spermatocyte and sertoli cells, Serum testosterone levels and a significant increase in the serum MDA level were found in the Bisphenol A group compared to the control group. The above parameters were compensated to the control level in the Bisphenol A + Vit E group. Conclusion: Vitamin E, as a strange antioxidant, could compensate many adverse the effects of Bisphenol A on the testis tissue, so it is suggested that it can be used as a potential supplement in case of BPA intoxication